Metal Surfaces Metal Surfaces - Montanari, Roberto; Kaciulis, Saulius (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This collection covers the physical and chemical phenomena of metal surfaces, including surface modifications and treatments. It is targeted at researchers working in materials science and also at newcomers to the research field of metal surfaces and surface analysis.